PROBLEMATIKA PENERIMAAN PESERTA DIDIK BARU (PPDB) DENGAN SISTEM ZONASI DI SEKOLAH DASAR (SD) KOTA PADANG - Reni manovtri; Ismira (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research describes the problems of accepting new students (PPDB) with the Zoning System in Padang City Elementary Schools. This type of research is qualitative. The presence of researchers is the main or key instrument. This research was conducted at 2 Padang City Elementary Schools. Data was obtained from school principals, teachers and prospective student parents. Data was collected by in-depth interviews, observation and documentation. Data were analyzed descriptively with interactive analysis, namely data reduction, data presentation, and drawing conclusions. Data validity with criteria and examination techniques, namely by extending the observation time and testing using triangulation techniques. The results of the research show that PPDB problems with the zoning system in Padang City Elementary Schools include: (1) Tight Competition and (2) inequality in facilities and resources.